Voices in the Forest: Unraveling REDD+ Discourse and Narratives in the Bale Eco-region, Ethiopia - Aklilu Bekele Chorito; Engdawork Assefa (Forest and Society)
REDD+ projects are viewed in environmental discourse as a centralized framework to assist ongoing initiatives to stop deforestation and forest degradation and to advance sustainable forest management. This case study captures the intricacy of REDD+ narratives and their practical implications through a qualitative methodology that includes in depth interviews and document analysis. We used snowball sampling to identify participants with diverse perspectives on REDD+ discourses. The interviews were conducted with 25 key informants who represented a variety of stakeholder groups. Discourse analysis was applied to examine contrasting perspectives of ecological modernization and civic environmentalism storylines and narratives on REDD+ implementation. Additionally, it utilized content analysis to explore diverse viewpoints on REDD+ key dimensions and strategic aspects to gain valuable insights from different stakeholder coalitions. We identified three primary discourse coalitions: promoters, moderators, and opponents. The promoters, predominantly consisting of government agencies and international organizations, view REDD+ as a market-driven, technocratic solution to climate change. The moderators, comprise mostly of regional authorities, universities and local institutions, who tend to advocate for a more balanced approach, emphasizing social justice, local empowerment, and sustainable livelihoods. Opponents primarily include the private sector, civil society networks, scholars, indigenous communities and small-scale farmers, express concerns about the potential negative impacts of REDD+, including on land tenure, cultural disruption, and increased inequality. Our analysis reveals the power dynamics at play, with dominant discourses often overshadowing local perspectives. We argue that a more nuanced understanding of these competing narratives is crucial for effective REDD+ implementation. By considering the diverse perspectives of stakeholders and addressing underlying power imbalances, it makes it possible to harness the potential of REDD+ to promote both environmental conservation and social equity in the Bale Eco-region.